Antara Ketepatan Saluran Distribusi dan Volume Penjualan - Yuhono, Agus (Jurnal Manajemen Riset Bisnis Indonesia, 2019)
Distribution channel is one important factor in the marketing mix, ie product, price, place, and promotion. It is an integral part of said place. The accuracy of distribution channels in general will help increasing the volume of sales which is the ultimate goal of marketing. This work is intended to determine the effect of the accuracy of the distribution channel to sales volume by taking the case of the PT Tirtamas Lestari. This study uses statistical methods to test causal through populations of bottled water sales at PT Tirta. The conclusion of this study is that the accuracy of the distribution channel significantly affects sales volume. However, note also that the distribution channel turned out to have a number of barriers that result in less optimal distribution channels in increasing sales volume. Kata Kunci: Saluran Distribusi, Volume Penjualan, Bauran Pemasaran, Pelayanan Prima